Sero-Epidemiological Investigation on Peste Des Petits Ruminants in Black Bengal Goats (Bangladesh Journal of Microbiology, 2008)
A natural outbreak suspecting PPR (peste des petits ruminants) was thoroughly investigated and confirmed by monoclonal antibody (mAb)-based enzyme immuno slide assay (EISA). Nasal discharge in early stage of disease course, diarrhoeic faeces and lung as a post-mortem sample was a source of sufficient virus to be detected by this technique. Convalescent polyclonal sera from the recovered animal diagnosed as PPR by EISA revealed high antibody titre by competitive-ELISA. It was found that EISA is suitable, sensitive and specific to confirm PPR infection in both field and laboratory conditions especially in developing country. In the affected houses morbidity and mortality rate was 74.13% and 54.83% respectively and observed high in the age group of 5-8 weeks, but sex difference was not significant. Early rainy season (July 2006) was the period of the present outbreak. Sero-positive animal closer to the outbreak area concluded that virus was circulating in the experimental area of Mymensingh district. Vaccinated sero-nagative animal could withstand the natural disease onset. Purchase of new animal from market and grazing in the same field with infected goats was the source of present outbreak.DOI: http://dx.doi.org/10.3329/bjm.v24i2.1260 Bangladesh J Microbiol, Volume 24, Number 2, December 2007, pp 143-145